2003
DOI: 10.1038/sj.ejcn.1601898
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cognitive function and mental performance in mild dehydration

Abstract: Dehydration is a reliable predictor of impaired cognitive status. Objective data, using tests of cortical function, support the deterioration of mental performance in mildly dehydrated younger adults. Dehydration frequently results in delirium as a manifestation of cognitive dysfunction. Although, the occurrence of delirium suggests transient acute global cerebral dysfunction, cognitive impairment may not be completely reversible. Animal studies have identified neuronal mitochondrial damage and glutamate hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(84 citation statements)
references
References 37 publications
0
78
2
4
Order By: Relevance
“…It is interesting to note that antihypertensive medication is currently prescribed against these very same hormones (Deedwania, 2007;Nesbitt, 2007). In 2002, a meeting was organized in Dortmund to study the physiological effects of mild dehydration, yet the majority of presentations showed the benefits of increased consumption of fluid, be it at the level of cognition (Wilson and Morley, 2003), exercise performance (Maughan, 2003), urolithiasis Beverage intake in the French F Bellisle et al (Siener and Hesse, 2003), urinary tract infection (Beetz, 2003), dental disease (Smith and Shaw, 2003), constipation (Arnaud, 2003) or even broncho-pulmonary infection (Kalhoff, 2003). Such reports are the outcome of scientific studies, rather than 'urban myths found on the Internet' (Negoianu and Goldfarb, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that antihypertensive medication is currently prescribed against these very same hormones (Deedwania, 2007;Nesbitt, 2007). In 2002, a meeting was organized in Dortmund to study the physiological effects of mild dehydration, yet the majority of presentations showed the benefits of increased consumption of fluid, be it at the level of cognition (Wilson and Morley, 2003), exercise performance (Maughan, 2003), urolithiasis Beverage intake in the French F Bellisle et al (Siener and Hesse, 2003), urinary tract infection (Beetz, 2003), dental disease (Smith and Shaw, 2003), constipation (Arnaud, 2003) or even broncho-pulmonary infection (Kalhoff, 2003). Such reports are the outcome of scientific studies, rather than 'urban myths found on the Internet' (Negoianu and Goldfarb, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In critical illness, it is recommended that daily energy intake is increased to match increased demands to the order of 20 -30 kcal kg 21 body mass [47,58,101]. Objective evidence demonstrating the benefit of matching energy demands with supply is lacking [105]; however, there are harmful consequences associated with over-and underfeeding [55,58,106].…”
Section: Feeding Wounded Soldiersmentioning
confidence: 99%
“…inability to carry out physical tasks, poor concentration and decreased vigilance) [21,22]. The long-term effects of both macro-and micro-nutrient imbalances include increased risk of vitamin and mineral deficiencies (potentially predisposing some individuals to an increased risk of stress fractures and rickets), obesity, hypertension, coronary heart disease, diabetes, osteoporosis and kidney failure.…”
Section: Contemporary Military Nutritionmentioning
confidence: 99%
“…Dehydration is common in older persons and is often made worse by inappropriate use of diuretics to treat pedal edema (46). Dehydration is associated with frailty, falls, syncope, poor cognition, disability and mortality (47)(48)(49)(50)(51).…”
mentioning
confidence: 99%